Carbon monoxide-releasing properties and DFT/TDDFT analysis of [Mn(CO)(3)(bpy)L]PF6 type novel manganese complexes - Ustun, Elvan; Koc, Sefika; Demir, Serpil; Ozdemir, Ismail (2016)
Novel manganese(I) carbonyl complexes of the general formula [Mn(CO)(3)(bpy)L]PF6 (bpy = 2,2-bipyridyl, L = N-(2-methylbenzyl)imidazoline, N-(3-methylbenzyl)imidazoline, N-(4-methylbenzyl)imidazoline, N-(2,4,6-trimethylbenzyl)imidazoline) were synthesized and characterized by analytical (LC-MS spectrometry and elemental analysis) and spectroscopic (H-1 NMR, C-13 NMR, cosy2D-NMR, infrared) methods. The CO-releasing properties of these complexes were investigated with myoglobin assay. The DFT/TDDFT calculations were made by ORCA package program with both BP86 and B3LYP functionals. (C) 2016 Elsevier B.V. All rights reserved.